2014
DOI: 10.1007/s00167-014-3214-z
|View full text |Cite
|
Sign up to set email alerts
|

Proximity of the axillary nerve during bicortical drilling for biceps tenodesis

Abstract: This study highlights the need for caution when drilling the posterior humeral cortex during biceps tenodesis, particularly during drilling at the superior insertion of PM as this is the location that poses the highest risk to the axillary nerve. To our knowledge, this is the first cadaveric study to radiologically assess the proximity of the axillary nerve to the positions of biceps tenodesis. Surgeons should therefore be cautious when performing bicortical drilling for biceps tenodesis, and a supero-lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
7
2
Order By: Relevance
“…In the subpectoral approach, it risks injury to the radial nerve 6 while in the suprapectoral approach, it risks injuring the axillary nerve. 7 Ding et al. 5 suggested that the safest biceps tenodesis placement was at the inferior aspect of the bicipital groove as it avoids penetrating both the axillary and radial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…In the subpectoral approach, it risks injury to the radial nerve 6 while in the suprapectoral approach, it risks injuring the axillary nerve. 7 Ding et al. 5 suggested that the safest biceps tenodesis placement was at the inferior aspect of the bicipital groove as it avoids penetrating both the axillary and radial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The position of the axillary nerve is at the level of the superior border of pectoralis major. 9,10 Malleting of the guide wire to breach the second cortex is done only as a precautionary method to avoid looping around any vital structure in the posterior aspect. The diameter of the hole is matched to the diameter of the tendon, usually w5.5 to 6 mm.…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, unicortical drilling with the all-suture anchor protects the axial nerve, which is at greater risk when using bicortical drilling. 22 Finally, suture tape reduces the risk of slippage and other complications sometimes seen with smaller-bore sutures. 23,24 In conclusion, this article presents a technique for a mini-open subpectoral biceps tenodesis using an onlay technique with an all-suture anchor preloaded with needles and suture tape.…”
Section: Tenodesis Site Preparationmentioning
confidence: 99%